아이트래킹을 활용한 인기 애니메이션 캐릭터의 시각적 주의에 관한 연구 - 황미경(Mi-Kyung Hwang); 권만우(Mahn-Woo Kwon); 박민희(Min-Hee Park); 은석함(Shuo-Han Yin) (한국콘텐츠학회 논문지, 19(6), 2019)
Visual perception information acquired through human eyes contains much information on how to view visual stimuli using eye tracking technology, it is possible to acquire and analyze consumer visual information as quantitative data. These measurements can be used to measure emotions that customers feel unconsciously, and they can be directly collected by numerically quantifying the character's search response through eye tracking. In this study, we traced the character's area of interest (AOI) and found that the average of fixation duration, count, average of visit duration, count, and finally the time to first fixation was analyzed. As a result of analysis, it was found that there were many cognitive processing processes on the face than the character's body, and the visual attention was high. The visual attention of attraction factor has also been able to verify that attraction is being presented as an important factor in determining preferences for characters. Based on the results of this study, further studies of more characters will be conducted and quantitative interpretation methods can be used as basic data for character development and factors to be considered in determining character design. 사람의 눈을 통해 획득된 시각정보는 시각적 자극을 어떻게 보는지에 대한 많은 정보를 포함하고 있는데, 아이트래킹기술을 활용하면 소비자의 시각정보를 정량적 데이터로 획득하여 분석가능하다. 이러한 측정은 소비자가 무의식적으로 느끼게 되는 감성 측정이 가능하며, 시선추적을 통한 캐릭터의 탐색반응을 계량적으로 수치화하여 직접 수집할 수 있다. 본 연구에서는 캐릭터의 관심영역(AOI)을 추적하여, 시선고정 도출 측정값 중 시선고정평균시간, 횟수, 시선방문평균시간, 횟수, 마지막으로 처음 시선고정이 일어난 평균시간을 분석하였다. 분석결과, 전체적으로 시선고정과 시선방문이 주로 이루어진 지점은 캐릭터의 몸매보다는 얼굴에서 많은 인지적 처리과정이 일어났으며 시각적 주의가 높게 나타났다. 또한 매력요소의 시각적 주의를 통해 매력요소가 캐릭터에 대한 선호도를 결정하는 중요한 요인으로 제시되고 있음을 검증할 수 있었다. 향후 본 연구결과를 토대로 더 많은 캐릭터의 추가 연구가 수행되어 정량적 해석 방법이 제시된다면 캐릭터 개발의 기초자료로 그리고 캐릭터디자인 결정시 고려해야 할 요소로 활용될 수 있을 것이다.